PENENTUAN KADAR ASAM LEMAK BEBAS PADA MINYAK JELANTAH DENGAN PENAMBAHAN ANTIOKSIDAN ALAMI KULIT PISANG RAJA (Musa sapientum) - Debora Patty; Pamella Mercy Papilaya; R L Karuwal (BIOPENDIX, 2017)
Background: Indonesia as one of agrarian countries rich in natural resources and has a variety of plants that have great potential to be utilized as a natural antioxidant, one of which is a banana. In the utilization of bananas is limited to the meat alone while the skin is only used as waste, whereas banana peels have a high value of benefits, it is evident that the banana skin contains high oxygen activity compared to meat. Method: The method used is Completely Randomized Design (RAL) with factorial pattern consisting of 5 treatments and 3 repetitions. The results were analyzed statistically with Anova test showed sig value. 0.000 <0.05 followed by Tukey test showing very real difference in each treatment. Results: The results showed that group P (3) was the best treatment group that decreased free fatty acid content in cooking oil with the addition of natural antioxidant of banana peel (Musa sapientum). Conclusion: The addition of natural antioxidant of banana skin effect in decreasing free fatty acids fatty acid content with average free fatty acid content with 1% b / b, 2% w / b and 3% b / b banana peel powder of 0 , 2928%, 0.2733% and 0.2370%.